0
$\begingroup$

Let $\Gamma$ be some group, and let $$\ell^2(\Gamma) := \{f : \Gamma \to \Bbb{C} \mid \sum_{\gamma \in \Gamma} |f(\gamma)|^2 < \infty\}.$$ Given $\gamma \in \Gamma$, define $u_\gamma : \ell^2(\Gamma) \to \ell^2(\Gamma)$ by $u_\gamma(f)(\eta) := f(\gamma^{-1} \eta)$. I am reading an expository paper in which in claims that $u_\gamma$ is a unitary operator and that $\gamma \mapsto u_\gamma$ defines a unitary representation (called the left regular representation; see page 7 of this). However, this seems to be a mistake. Shouldn't $u_\gamma$ actually be $u_\gamma (f)(\eta) := f(\gamma \eta)$? Defined the former way, I wasn't able to show that $\gamma \mapsto u_\gamma$ is a homomorphism, but I was able to show that it is a homomorphism if defined the later way. Am I misunderstanding something?

EDIT:

Given the second way of construing the left regular representation, it is easy to show that $u_\gamma$ is invertible with inverse $u_{\gamma^{-1}}$. However, when I try to show that $u_{\gamma}^{\ast} = u_{\gamma^{-1}}$ (i.e., that $u_{\gamma}$ is unitary), I run into some difficulties. I could use some help with showing that $u_{\gamma}$ is unitary.

$\endgroup$
  • 2
    $\begingroup$ $$u_{\gamma\delta}f(\eta) = f((\gamma\delta)^{-1}\eta) = f(\delta^{-1}\gamma^{-1}\eta) = u_\delta f(\gamma^{-1}\eta) = u_\gamma(u_\delta f)(\eta),$$hence $u_{\gamma\delta} = u_\gamma\circ u_\delta$. Note that for $\Gamma = (\mathbb R,+)$ you have $\ell^2(\Gamma) = L^2(\mathbb R)$ and $u_\gamma f(x) = f(x-\gamma)$, so $u_\gamma$ is translation by $\gamma$. So, the $u_\gamma$ you have here is just a generalization of the concept of translation. $\endgroup$ – amsmath Jun 5 at 13:32
  • $\begingroup$ The computation by @amsmath shows why the definition using $\gamma^{-1}$ works. You should also check why your proposed definition doesn't work; an analogous computation gives $u_\gamma(u_\delta(f))=u_{\delta\gamma}(f)$. $\endgroup$ – Andreas Blass Jun 5 at 16:03
1
$\begingroup$

The comments explain why the representation defined by $\gamma\mapsto u_\gamma$ with $(u_\gamma f)(\eta)=f(\gamma^{-1}\eta)$ is indeed a homomorphism.

To see that this representation is unitary, it suffices to show that $\langle u_\gamma f,u_\gamma g\rangle=\langle f,g\rangle$ for all $f,g\in \ell^2\Gamma$ (this shows that $u_\gamma$ is an isometry, and thus a unitary since it is invertible). And to show this, it suffices to consider $f=\delta_\mu$, $g=\delta_\nu$ for some $\mu,\nu\in\Gamma$, where $\delta_\mu(\gamma)=1$ if $\gamma=\mu$ and $=0$ otherwise (since $\{\delta_\gamma\mid\gamma\in\Gamma\}$ is an orthonormal basis of $\ell^2\Gamma$). And seeing this is easy: \begin{align*} \langle u_\gamma\delta_\mu,u_\gamma\delta_\nu\rangle&=\langle\delta_{\gamma\mu},\delta_{\gamma\nu}\rangle\\ &=\left\{\begin{array}{lcl} 1&:&\gamma\mu=\gamma\nu,\\ 0&:&\text{otherwise}, \end{array}\right. \\ &=\langle\delta_\mu,\delta_\nu\rangle. \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.